Research on Position Control Method of All-axle Steering System for Autonomous-rail Rapid Tram - HUANG Song; LIU Xiaocong; PENG Jing; XIAO Lei; SU Aijun; LI Xiaoguang (Kongzhi Yu Xinxi Jishu)
Aiming at redundant control strategy of all-axle steering system for autonomous-rail rapid tram, a controlling method based on cylinder displacement was presented. Direct kinematics model of steering device of the vehicle-bridge is build, which is actually a plane five-bar linkages. Newton-Raphson method is used to obtain the solution of direct kinematics. The direct kinematics model is verified by simulations with Matlab and ADAMS. Based on this, a closed-loop PID control strategy is established. The cylinder, s displacement of the axle driven by steering wheel is detected to obtain the steering angle, which is treated as the input arguments of the vehicle control method so as to obtain the target steering angles of the other axis of the vehicle. And then closed-loop control of the steering system is accomplished by digital PID algorithm.Validation of the control method is carried out by the experiment of the closed-loop PID control strategy and substantial vehicle test.